Karakter Pemimpin Generasi Milenial: Survei Mahasiswa Pendidikan Sejarah - Muhammad Azmi; Siti Marfuah (Universitas Sebelas Maret, 2022)
The millennial generation is a member of society who has received a gift in the midst of globalization. All aspects of their lives cannot be separated from their gadgets and the rapid flow of information in cyberspace. This certainly has an influence on the formation of their perspective on politics. This paper provides an overview of the perspectives of students of the History Education Study Program, FKIP Mulawarman University about the ideal leader in the eyes of the millennial generation. The survey results show that their ideal leader is an open, critical and able to communicate with the millennial generation, especially through cyberspace.